Review of Moser, Keith, and Ananta Ch. Sukla (eds). Imagination and Art: Explorations in Contemporary Theory. Brill, 2020. (ENTHYMEMA, 2022)
Review of Moser, Keith, and Ananta Ch. Sukla (eds). Imagination and Art: Explorations in Contemporary Theory. Brill, 2020.